(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This study provides a comprehensive exploration of the cultural relationship between India and China, emphasizing the richness and diversity that characterize their historical and contemporary interactions. The historical narrative delves into the millennia-old cultural exchanges, emphasizing the impact of religious and philosophical ideas such as Buddhism that originated in India and found profound resonance in China. The Silk Road served as a conduit for not only trade but also the exchange of art, literature, and scientific knowledge, fostering a shared cultural heritage. The study also explores the role of language in shaping cultural identities and fostering communication between the peoples of India and China. The impact of globalization on cultural dynamics is examined, considering how modernization and technological advancements have influenced cultural exchanges between India and China.